Blue Nevus of the Hard Palate: The Importance of a Careful Examination in an Emergency Setting. (15th February 2022) - Tavares, Ana Teresa; Pereira, André; Pimentel, João; Prates, Marcelo; Fonseca, Luís; Marques, Maria Rosário; Proença, Francisco
Abstract : Oral common blue nevus is an asymptomatic, benign, rare, pigmented lesion and sometimes clinically indistinguishable from other pigmented lesions such as the cellular blue nevus or early-stage malignant melanoma. Since it shows clinical similarities with a malignant lesion and with cellular blue nevus that can itself suffer malignant transformation, the decisive diagnosis is crucial for adequate treatment, follow-up, and prognosis. Diagnosis confirmation is given by histological analysis, the reason why most oral pigmented lesions are excised. The following case presents an asymptomatic oral pigmented lesion of the hard palate discovered during observation in an emergency setting due to an abscess of dental origin. The lesion was fully excised, and histological examination reported a "common blue nevus." In this case, we intend to present a rare lesion of the oral cavity and the importance of performing a routine oral examination when given a chance as a preventive approach.